A Silicon Pancreatic Beta Cell for Diabetes - Georgiou,P; Toumazou,C (IEEE Transactions on Biomedical Circuits and Systems, 2007)
The paper will consider how silicon devices such as ion-sensitive field effect transistors can be used to model metabolic functions in biology. In a first example, a biologically inspired silicon beta cell is presented to serve as the main building block of an artificial pancreas. This is to be used for real-time glucose sensing and insulin release for diabetics. This system presents the first silicon implementation of a metabolic cell capable of exhibiting variable bursting behavior upon glucose stimulation. Based on the Hodgkin and Huxley formalism, this approach achieves dynamics similar to that of biological beta cells by using devices biased in the subthreshold regime. In addition to mimicking the physiological behavior of the beta cell, the circuit achieves good power efficiency, measured to be 4.5 uW